Skin manifestations and human immunodeficiency virus infection in the Tigray region, Ethiopia: Implications for clinical management and epidemiologic surveillance - Aldo Morrone; Elva Abril; Ilaria Cavallo; Francesca Sivori; Isabella Sperduti; Viviana Lora; Giovanna D'Agosto; Elisabetta Trento; Martina Pontone; Arianna Mastrofrancesco; Abraham Getachew Kelbore; Frehiwot Daba Gutema; et al. (Wiley, 2024)
Abstract Background Patients with human immunodeficiency virus (HIV) infection may present a large variety of skin manifestations, often associated with significant morbidity. In turn, dermatological diseases may represent an early sign of HIV infection, particularly in resource‐limited settings. Objectives This study aimed to assess the spectrum of dermatological diseases and their potential value as clinical proxies for the early detection and management of HIV in a rural region of Ethiopia. Methods The study was performed on a population of 67,161 patients with skin diseases attending the Italian Dermatological Center in Mekele, Tigray region, Ethiopia. HIV infection was diagnosed in 1892 individuals (1065 female), all naïve to antiretroviral therapy. Results Infectious skin diseases were present in 57.2% of the total HIV population. Among the infectious skin manifestations, dermatophytosis (20.5%), impetigo (5.9%), candidiasis (4.7%) and molluscum contagiosum (4.7%) were significantly more represented in patients with HIV infection (p < 0.001). Regarding the noninfectious manifestations, pruritus and atrophy of the papillae on the tongue were significantly associated with HIV (p < 0.001). Notably, females had a significantly higher incidence of dermatophytosis and seborrheic dermatitis as compared to their male counterparts (p < 0.001), whereas scabies, psoriasis and leishmaniasis were significantly more frequent in males (p < 0.001). Conclusions Skin manifestations are common in HIV patients, often reflecting compromised immune status. In addition, Dermatophytosis and pruritus were the most frequently reported manifestations of HIV, thus representing useful clinical proxies to raise the suspicion of an underlying HIV infection. Besides, gender differences in skin manifestations should also be considered in the clinical evaluation.